THE ROLE OF SOPHIE NEVEU IN THE DA VINCI CODE: "A STUDY OF LIBERAL FEMINISM" - Budiyanto Suretno, Willis; Halomoan, Hot Saut (Bhumantara, 2026)
This study analyzes the character of Sophie Neveu in The Da Vinci Code (2006), directed by Ron Howard, through the theoretical lens of liberal feminism as articulated by John Stuart Mill. The primary objective is to examine how Sophie embodies the principles of gender equality, rationality, educational rights, freedom of choice, and resistance to discrimination. Employing a descriptive qualitative approach with a film-text analysis method, this research focuses on the character’s dialogues, narrative functions, and behavioral actions within the film. The findings reveal that Sophie Neveu is portrayed as an intelligent and autonomous woman with strong analytical and logical reasoning abilities. On several occasions, she demonstrates intellectual superiority over male characters, particularly Robert Langdon, and plays a crucial role in the progression of the plot through her code-breaking skills and independent decision-making. However, despite her competence, the film also depicts persistent gender-based discrimination imposed by authority figures and male counterparts. Overall, the study concludes that The Da Vinci Code, through the characterization of Sophie Neveu, implicitly upholds the core values of liberal feminism, affirming that women possess equal intellectual and moral capacities and deserve equal rights and opportunities in all aspects of life.